2012
DOI: 10.1108/01604951311322039
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and use of e‐journals by IIT Delhi and Delhi University library users

Abstract: u ul l ly y y-S S Se e ep p p t t te e em m mb b be e er r r, , , 2 2 20 0 01 1 12 2 2, , , I I Is s ss s su u ue e e-3 3 3 w w ww w ww w w.. .i i ij j jo o od d dl l ls s s.. .i i in n n (((I I IS S SS S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…Of those (90.9%) who responded in affirmation, roughly n=106 (75.7%) were from College of Medicine, while n=34 (24.3%) were from College of Dentistry. The finding that 90.9 % of respondents had heard of the databases before, concurred with the findings by Chirra and Madhusudhan (2009), Kwafoa, Osman, and AffulArthur (2014), Nisha and Ali (2012) that recorded over 90% awareness of the databases in their institutions. This also indicates that the students got benefited with the library information literacy programs organized periodically to make them aware of the available resources.…”
Section: Knowledge Of Electronic Resourcessupporting
confidence: 87%
See 1 more Smart Citation
“…Of those (90.9%) who responded in affirmation, roughly n=106 (75.7%) were from College of Medicine, while n=34 (24.3%) were from College of Dentistry. The finding that 90.9 % of respondents had heard of the databases before, concurred with the findings by Chirra and Madhusudhan (2009), Kwafoa, Osman, and AffulArthur (2014), Nisha and Ali (2012) that recorded over 90% awareness of the databases in their institutions. This also indicates that the students got benefited with the library information literacy programs organized periodically to make them aware of the available resources.…”
Section: Knowledge Of Electronic Resourcessupporting
confidence: 87%
“…In his study of graduate students, Cothran (2011) claimed that academic search engines such as Google scholar and CiteSeers were used more as compared to subscribed databases because the users found them easy to learn, navigate and use. According to Nisha and Ali (2012), relevancy, currency and rich content also influence the use of a particular database.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study shows about big range of e-resources and services offered by the IITs libraries to their users. Nisha & Ali 16 in their research paper focused about use of e-journals by IIT-Delhi and Delhi university library users and result shows that e-resources offered by the libraries are much beneficial for the library users. Study illustrate various critical issues such as slow downloading speed, non-availability of specific issue of journal, lack of training, regarding e-services, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many scholarly works have been done on awareness of the various electronic databases offered by many university libraries worldwide. Studies by Nisha and Ali (2013), Chirra and Madhusudhan (2009) all revealed that clients were aware of and used the electronic databases available to them. In their study, for instance, Chirra and Madhusudhan (2009) confirmed the use of electronic journals by doctoral research scholars of Goa University, India.…”
Section: Literature Reviewmentioning
confidence: 99%